EXPLORING THE ACQUISITION OF SPOKEN ARABIC VARIETIES: INSIGHTS FROM NOAM CHOMSKY’S GENETIC-COGNITIVE THEORY - Husnaini Jamil; Asbarin; Mukhlishoh (ALSINATUNA, 2023)
This study investigates the implications and implementation of cognitive genetic theory in acquiring various spoken Arabic varieties, drawing upon Noam Chomsky's cognitive genetic perspective. The research focuses on MTs Al-Irsyad Tengaran in Batu City, chosen due to its majority population of Yemeni Arab descendants known as Jeme'eh. The study explores the impact of this demographic on the Arabic language used for communication, which displays slight differences from general Arabic usage. Employing qualitative descriptive research methodology, data is collected through interviews, observations, and documentation. The analysis follows the Miles and Huberman techniques, encompassing data collection, reduction, presentation, and conclusion. Findings reveal four spoken Arabic varieties among the students: word variety (11 instances), phrases (5 instances), sentences (3 instances), and clauses (1 instance). Importantly, students acquire these language variations incidentally, relying solely on their cognitive abilities and Language Acquisition Device (LAD). These results align with Chomsky's cognitive genetic theory, which suggests that children can acquire language without explicit instruction. This research contributes to the development of psycholinguistic science, enhances practical understanding of speech patterns, provides a valuable reference for future researchers, and enriches readers' knowledge, particularly within Noam Chomsky's cognitive genetics.